Risk factors associated with developing branch retinal vein occlusion among enrollees in a United States managed care plan - Newman-Casey, Paula Anne; Stem, Maxwell; Talwar, Nidhi; Musch, David C; Besirli, Cagri G; Stein, Joshua D (Ophthalmology (Rochester, Minn.), 2014)
To determine risk factors associated with development of a branch retinal vein occlusion (BRVO) among a large group of managed-care plan beneficiaries in the United States. Retrospective, longitudinal cohort study. All beneficiaries age ≥55 years continuously enrolled for ≥2 years in a managed care network from 2001-2009 who had ≥2 visits to an eye care provider. Multivariable Cox regression analyses identified sociodemographic factors, ocular and nonocular conditions associated with incident BRVO. Hazard of incident BRVO with 95% confidence interval (CI). Of the 492,488 enrollees who met inclusion criteria, 2283 (0.5%) developed incident BRVO. After adjustment for confounding factors, blacks (adjusted hazard ratio [aHR], 1.43; CI, 1.19-1.73; P = 0.0001) had a 43% increased hazard of BRVO relative to non-Hispanic whites. Enrollees with hypertension (HTN) alone (aHR, 1.78; CI, 1.36-2.32; P < 0.0001) or HTN along with other metabolic syndrome components (diabetes mellitus [DM] and hyperlipidemia; aHR, 1.44; CI, 1.12-1.84; P = 0.005) had an increased hazard of developing a BRVO compared with those with none of these conditions. Disease severity was important; enrollees with end-organ damage caused by HTN had a 107% increased hazard of developing BRVO compared with enrollees without HTN (aHR, 2.07; CI, 1.75-2.45; P < 0.0001). Although there was no association between DM without end-organ damage and BRVO (aHR, 0.92; CI, 0.81-1.04; P = 0.2), individuals with end-organ damage from DM had a 36% increased hazard of BRVO (aHR, 1.36; CI, 1.18-1.57; P < 0.0001) compared with those without DM. Although cerebrovascular accident was associated with an increased hazard of developing BRVO (aHR, 1.34; CI, 1.19-1.52; P < 0.0001), other diseases of the vascular system (deep venous thrombosis/pulmonary embolism, peripheral vascular disease, hypercoagulable state, myocardial infarction) or anticoagulant use did not increase the risk of BRVO (P > 0.10 for all comparisons). Both HTN and end-organ damage from DM contribute to arteriosclerosis, atherosclerosis, and endothelial dysfunction, which seem to be major risk factors for BRVO. Ophthalmologists should emphasize to patients and their primary physicians the importance of effectively managing systemic medical conditions associated with BRVO.